Genetic polymorphism of CYP1A1 and CYP2D6 in populations of Buryats, Teleuts and Russians of Eastern Siberia - L. E. Tabikhanova; L. P. Osipova; T. V. Churkina; E. N. Voronina; M. L. Filipenko (Вавиловский журнал генетики и селекции)
The study of the gene polymorphism of the system of biotransformation of xenobiotics is an important area of modern medical and genetic research. The aim of this work is to study the frequency of the alleles of the CYP1A1 (A2455G (*2C), rs1048943), CYP2D6 (A2549del (*3), rs35742686); G1846A (*4), rs3892097) genes of Teleuts (n = 115), Eastern Buryats (n = 132), Western Buryats (n = 280), their Métis (n = 56), and Russians of East Siberia (n = 122). Genotyping was performed using real-time PCR with competitive TaqMan allele-specific probes. The frequency of the CYP1A1*2C (2455G) allele was 28.8 % in the Eastern Buryat, 34.6 % in the Western Buryat, 16.7 % in the Teleut, and 31.3 % in the Métis cohort. The frequency of CYP1A1*2C (2455G) in the Russians of Eastern Siberia (4.1 %) corresponds to the frequency range found in European populations. A high-frequency occurrence of CYP1A1*2C (2455G) among Buryats and Teleuts may be indicative of a higher population-wide risk of diseases influenced by technogenic pollutants – substrates of CYP1A1. The CYP2D6*3 (2549del) allele was not detected in cohorts of indigenous populations, among Russians it was 0.4 %, and it was 2.7 % among Métis. The frequency of CYP2D6*4 (1846A) in Eastern and Western Buryats was 5.3 % and 4.3 %, respectively, for Teleuts it was 7.4 %. It was significantly higher in the Russian population (12 %), and among Métis (9.8 %). The obtained data makes it possible to predict a reduced risk of side effects of drugs and cancer associated with CYP2D6*3 (2549del) and CYP2D6*4 (1846A) in the Buryat and Teleut populations. However, metisation introduces new polymorphic variants into indigenous populations, shifts gene frequencies and changes the degree of risks.